Goal setting and knowledge generation through health policy and systems research in low- and middle-income countries - Xue, Jiayin (BioMed Central, 2014)
The importance of health policy and systems research (HPSR) and its role in aiding health system reforms has been increasingly recognized in recent years within the World Health Organization (WHO). An assessment of the 71 WHO Country Cooperation Strategies (CCS) that are publicly available and were published in English in 2012 was completed to determine the extent to which HPSR goals are incorporated at the global level. A review was then conducted using a Medline database search to determine the number of articles published by countries with HPSR goals. Sixty-six out of the 71 (93%) available CCS describe HPSR as an objective or strategy for achieving health system priorities. However, only 52 out of the 66 countries (79%) have any publications involving HPSR during their most recent CCS cycle. This suggests that although health systems strengthening through HPSR is increasingly emphasized by the WHO and country health ministries, actual HPSR progress may still be lacking. There is a need and an opportunity for the WHO and other global health agencies to focus on providing the necessary tools and building HPSR capacity in low- and middle-income countries.